Eletroforese capilar: um método para determinação de hipoglicemiantes como adulterantes em formulações herbáreas usadas no tratamento do diabetes - Ferreira, Marlise (2012)
The popularity of herbal medicines as adjuncts in the treatment of diabetes mellitus, has increased in recent years. However, recent studies have demonstrated the presence of synthetic drugs, as adulterants, in these formulations, what can cause serious problems to the health of the patient, since interactions and pharmacological effects are unpredictable. This work describes the development of a method for the simultaneous determination of metformin, glibenclamide, gliclazide and chlorpropamide employing capillary zone electrophoresis (CZE) with contactless conductivity detection (C4D). The work was carried out using a capillary electrophoresis system built in the laboratory. The optimized conditions for the determination of adulterants in herbal medicines by CZE-C4D were the following: 20 mmol L-1 sodium acetate at pH 10.0 as working electrolyte, separation potential of -15kV, separation temperature of 25ºC, indirect conductivity detection operating at 400 kHz and amplitude wave of 2 Vpp, hydrodynamic injection by gravity (20 cm left side elevation for 60 s). The method was validated and applied to the determination of hypoglycemics in pharmaceutical formulations commercialized by compounding pharmacies in Brazil. The method allows the identification of adulterants and its quantification from 0.24 mg to metformin, 0.15 mg to glibenclamide, 0.33 mg to gliclazide and 0.24 mg to chlorpropamide.